2018
DOI: 10.1002/nop2.171
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depressive symptoms in patients with acute coronary syndrome undergoing percutaneous coronary intervention: A prospective cohort study

Abstract: AimTo identify the association between possible factors and depression among post‐percutaneous coronary intervention patients with acute coronary syndrome.DesignProspective cohort study.MethodsSixty‐eight post‐percutaneous coronary intervention patients with acute coronary syndrome were enrolled between January 2016 ‐ June 2017. The Hospital Anxiety and Depression Scale scores at 1–3 months after discharge were regressed onto uncertainty in illness and other clinical factors based on the Roy Adaptation Model.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The correlation test results are also due to the personal control aspect of the disease perception variable, which explains a person's beliefs about healing and self-control against disease. Beliefs about healing and self-control are the aspects that most influence how anxious a person feels [40]. Therefore, health care professionals must increase patients' belief in healing diseases to reduce their anxiety [41].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation test results are also due to the personal control aspect of the disease perception variable, which explains a person's beliefs about healing and self-control against disease. Beliefs about healing and self-control are the aspects that most influence how anxious a person feels [40]. Therefore, health care professionals must increase patients' belief in healing diseases to reduce their anxiety [41].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that chronic physical health conditions such as obesity, diabetes, cancer, cardiovascular disease, chronic respiratory diseases, chronic kidney and liver diseases, autoimmune conditions, HIV, hepatitis, and frailty present risk for severe COVID-19 infection [ 4 ]. Furthermore, mental health problems and conditions such as major depression, schizophrenia spectrum conditions, psychosis, anxiety disorders, and bipolar affective disorders are commonly comorbid among various chronic physical health conditions, including diabetes, cancer, cardiovascular disease, chronic respiratory diseases, arthritis, and inflammatory bowel disorders [ 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. The co-occurrence of physical and mental health issues results from an interplay of biological factors (e.g., increased inflammatory response), genetic predisposition, behavioral factors such as poor diet, physical inactivity, or substance use, and psychosocial factors such as illness experience [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, early postoperative pain may cause negative emotions and fear of activity, which may lead to limitations in physical activity [ 35 ]. A prospective cohort study found that some patients experienced deteriorated mental health after discharge, and psychological symptoms were more negative at 1 month after discharge compared with other periods resulting from uncertainties during illness and patients feeling annoyed by troublesome tasks after discharge [ 36 ]. Overall, the comprehension of symptom patterns requires further exploration to better meet the management needs of different patients at different times, improve quality of survival, and avoid adverse events.…”
Section: Introductionmentioning
confidence: 99%